2020
DOI: 10.21873/anticanres.14519
|View full text |Cite
|
Sign up to set email alerts
|

Redox-related Molecular Mechanism of Sensitizing Colon Cancer Cells to Camptothecin Analog SN38

Abstract: Background/Aim: The aim of this study was to elucidate the possibility of sensitizing colon cancer cells to the chemotherapeutic drug SN38 and investigate its mechanism of action after combined treatment with electroporation (EP). Materials and Methods: Cells were treated with SN38, EP and their combination for 24/48 h. The cell viability, actin cytoskeleton integrity, mitochondrial superoxide, hydroperoxides, total glutathione, phosphatidyl serine expression, DNA damages and expression of membrane ABC transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…As reported previously, the generation of ROS is associated with tumor cell death with both DSF [35] and SN-38 [36] treatments. We wanted to evaluate whether treatment with the DSF+SN-38 combination would increase ROS generation.…”
Section: Intracellular Reactive Oxygen Species (Ros) Generationsupporting
confidence: 73%
“…As reported previously, the generation of ROS is associated with tumor cell death with both DSF [35] and SN-38 [36] treatments. We wanted to evaluate whether treatment with the DSF+SN-38 combination would increase ROS generation.…”
Section: Intracellular Reactive Oxygen Species (Ros) Generationsupporting
confidence: 73%
“…For example, triterpene saponin ardisiacrispin B and epunctanone exerted cytotoxic effects partly via ferroptosis in resistant HCT116 p53−/− colon adenocarcinoma cells ( 6 , 7 ). By inducing ferroptosis and apoptosis, electroporation increased the sensitivity of CC cells to camptothecin analog SN38 ( 8 ). Omega-3 polyunsaturated fatty acids (n-3 PUFA) and highly fermentable fiber may induce ferroptosis to reduce the risk of colorectal cancer ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments showed that EP sensitized colon cancer cells to the camptothecin analogue, SN38, by changing the expression of ABC transporters and disrupting the integrity of the cytoskeleton. The chemosensitizing effect was due to the induction of oxidative stress and apoptotic/ferropoptotic cell death [ 101 ]. Promising results from in vivo experiments highlighted the importance of the use of ECT in the treatment of colon cancer, where electropermeabilization significantly increased the intratumoral content of bleomycin and cisplatin [ 102 ].…”
Section: Treatment Of Solid Tumors With Ectmentioning
confidence: 99%